To what extent does the corporate persona impinge upon the ethical self? An insight into the legal sector and the oil and gas industry in Singapore - Jeyaraj, Indumathi (2017)
Ethical dilemmas, set within the corporate landscape, potentially involves a conflict between two forces, one being the corporate persona that one assumes and the other being one’s ethical self. The central tenet of the dissertation is to explore the extent to which the corporate self impinges upon one’s ethical self. Its focus has been streamlined to consider the realities of working in the legal sector and the oil and gas (O&G) industry in Singapore. Kantian ethics, more specifically, Kant’s second formulation of the categorical imperative, dictates that a person ought not to be treated as the means to an end but rather an end in itself. Gleaning from this, it is interesting to consider whether the ethical self is respected in the work realm.